In a Model of Batten Disease, Palmitoyl Protein Thioesterase-1 Deficiency Is Associated with Brown Adipose Tissue and Thermoregulation Abnormalities - Khaibullina, Alfia; Kenyon, Nicholas; Guptill, Virginia; Quezado, Martha M.; Wang, Li; Koziol, Deloris; Wesley, Robert; Moya, Pablo R.; Zhang, Zhongjian; Saha, Arjun; Mukherjee, Anil B.; Quezado, Zenaide M.N. (PLOS ONE, 2012)
Infantile neuronal ceroid lipofuscinosis (INCL) is a fatal neurodegenerative disorder caused by a deficiency of palmitoyl-protein thioesterase-1 (PPT1). We have previously shown that children with INCL have increased risk of hypothermia during anesthesia and that PPT1-deficiency in mice is associated with disruption of adaptive energy metabolism, downregulation of peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), and mitochondrial dysfunction. Here we hypothesized that Ppt1-knockout mice, a well-studied model of INCL that shows many of the neurologic manifestations of the disease, would recapitulate the thermoregulation impairment observed in children with INCL. We also hypothesized that when exposed to cold, Ppt1-knockout mice would be unable to maintain body temperature as in mice thermogenesis requires upregulation of Pgc-1α and uncoupling protein 1 (Ucp-1) in brown adipose tissue. We found that the Ppt1-KO mice had lower basal body temperature as they aged and developed hypothermia during cold exposure. Surprisingly, this inability to maintain body temperature during cold exposure in Ppt1-KO mice was associated with an adequate upregulation of Pgc-1α and Ucp-1 but with lower levels of sympathetic neurotransmitters in brown adipose tissue. In addition, during baseline conditions, brown adipose tissue of Ppt1-KO mice had less vacuolization (lipid droplets) compared to wild-type animals. After cold stress, wild-type animals had significant decreases whereas Ppt1-KO had insignificant changes in lipid droplets compared with baseline measurements, thus suggesting that Ppt1-KO had less lipolysis in response to cold stress. These results uncover a previously unknown phenotype associated with PPT1 deficiency, that of altered thermoregulation, which is associated with impaired lipolysis and neurotransmitter release to brown adipose tissue during cold exposure. These findings suggest that INCL should be added to the list of neurodegenerative diseases that are linked to alterations in peripheral metabolic processes. In addition, extrapolating these findings clinically, impaired thermoregulation and hypothermia are potential risks in patients with INCL.